Physical Mapping of Bread Wheat Chromosome 5A: An Integrated Approach. Issue 3 (1st November 2015) - Barabaschi, Delfina; Magni, Federica; Volante, Andrea; Gadaleta, Agata; Šimková, Hana; Scalabrin, Simone; Prazzoli, Maria Lucia; Bagnaresi, Paolo; Lacrima, Katia; Michelotti, Vania; Desiderio, Francesca; Orrù, Luigi; et al.
Abstract : The huge size, redundancy, and highly repetitive nature of the bread wheat [ Triticum aestivum (L.)] genome, makes it among the most difficult species to be sequenced. To overcome these limitations, a strategy based on the separation of individual chromosomes or chromosome arms and the subsequent production of physical maps was established within the frame of the International Wheat Genome Sequence Consortium (IWGSC). A total of 95, 812 bacterial artificial chromosome (BAC) clones of short‐arm chromosome 5A (5AS) and long‐arm chromosome 5A (5AL) arm‐specific BAC libraries were fingerprinted and assembled into contigs by complementary analytical approaches based on the FingerPrinted Contig (FPC) and Linear Topological Contig (LTC) tools. Combined anchoring approaches based on polymerase chain reaction (PCR) marker screening, microarray, and sequence homology searches applied to several genomic tools (i.e., genetic maps, deletion bin map, neighbor maps, BAC end sequences (BESs), genome zipper, and chromosome survey sequences) allowed the development of a high‐quality physical map with an anchored physical coverage of 75% for 5AS and 53% for 5AL with high portions (64 and 48%, respectively) of contigs ordered along the chromosome. In the genome of grasses, Brachypodium [ Brachypodium distachyon (L.) Beauv.], rice ( Oryza sativa L.), and sorghum [ Sorghum bicolor (L.) Moench] homologs of genes on wheat chromosome 5A were separated into syntenic blocks on different chromosomes as a result of translocations and inversions during evolution. The physical map presented represents an essential resource for fine genetic mapping and map‐based cloning of agronomically relevant traits and a reference for the 5A sequencing projects.